EFEKTIVITAS MEDIA BUKU CERITA BERGAMBAR DALAM MENINGKATKAN SOSIAL EMOSIONAL ANAK USIA 5-6 TAHUN DI PAUD CISEENG BOGOR - Puji Yulianti; Siti Kemalasari (LPPM Universitas Bina Bangsa, 2023)
This research aims to improve the social emotional aspects of children aged 5-6 years through the picture story book method. The research method used is experimental research. The population used in the research was 10 students consisting of 6 men and 4 women. This data collection technique uses observation and documentation interview techniques. Meanwhile, the technical data analysis is carried out quantitatively. After the action was carried out, the posttest average was 76.7, while the pretest average was 54.4. Similarly, based on hypothesis testing using the t-test, namely the Independent T Test, the value of t count is 9.731. This value is greater than t table at a significance level of α < 0.050. T table 0.050 is 2.262. Then Ho is rejected and H1 is accepted, this proves that t count is greater than t table, meaning that the picture story book method can improve children's social emotionality